STUDI PENGGUNAAN VISUAL STUDIO 6.0 UNTUK PENGEMBANGAN SISTEM INFORMASI BERKELAS ENTERPRISE - Setiabudi, Djoni Haryadi; Gunawan, Ibnu (Institute of Research and Community Outreach - Petra Christian University, 2003)
This research is is about the study of capabilities dan peroformance of Ms Visual Studio in order to develop an enterprise application beside of to search